Apoptosis in an interleukin-2-dependent cytotoxic T lymphocyte cell line is associated with intracellular acidification. Role of the Na(+)/H(+)-antiport - Li, J; Eastman, A (The Journal of biological chemistry, 1995)
Apoptosis is a form of cell death associated with DNA fragmentation and chromatin condensation. We recently established that intracellular acidification occurred during apoptosis following cytotoxic insult. The current studies were designed to determine whether intracellular acidification was more generally associated with apoptosis, specifically in a model of growth factor withdrawal. Upon withdrawal of interleukin-2, CTLL-2 cells accumulated in the G1 phase of the cell cycle and started to fragment their DNA around 12 h concurrent with both decreased pH and increased Ca2. Chelation of Ca2+ did not inhibit DNA digestion, whereas incubation with a calcium ionophore prevented both acidification and DNA digestion. Hence, acidification rather than increased Ca2+ was associated with apoptosis. The acidified cells represented a discrete population up to 0.7 pH units below normal. The extent of acidification depended upon the extracellular pH; above pH 6.3, intracellular pH was significantly below extracellular pH, whereas below pH 6.3, the cells still regulated their pH. Inhibition of the Na+/H(+)-antiport prevented the apoptotic cells from regulating their intracellular pH under these acidic conditions. These intracellular pH under these acidic conditions. These results demonstrate that apoptotic cells retain a functional antiport but that its set-point has changed. Many survival factors are known to phosphorylate and activate the antiport, hence apoptosis is likely to be associated with dephosphorylation. Although acidification always occurred during apoptosis, maintaining intracellular pH above 7.2 did not prevent apoptosis, suggesting that an acid pH is not essential for apoptosis. We hypothesize that other critical regulators of apoptosis must be subject to dephosphorylation.